2014
DOI: 10.1039/c4nr03200d
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of magnetic, superhydrophobic, non-stick, two-phase Cu–Ni foam films and their enhanced performance for hydrogen evolution reaction in alkaline water media

Abstract: Two-phase Cu-Ni magnetic metallic foams (MMFs) with tunable composition have been prepared by electrodeposition taking advantage of hydrogen co-evolution as a source of porosity. It is observed that Ni tends to deposit inside the porous network defined by the Cu building blocks. Contact angle measurements reveal that the prepared porous films show a remarkable superhydrophobicity (contact angle values larger than 150°) and a non-sticking property to aqueous droplets. This behavior is predominately ascribed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 66 publications
1
69
0
Order By: Relevance
“…A classic approach to developing an active electrode with earth‐abundant elements on the basis of the Sabatier principle is by mixing elements with lower and higher intermediate binding energies. A consistent example is Ni−Cu, which shows a greater HER performance than Ni and Cu in alkaline conditions 93, 94, 95, 96, 97. Another promising material is Ni−Mo;98, 99, 100, 101 however, there have been issues associated with its low dispersion of the active surface.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 95%
“…A classic approach to developing an active electrode with earth‐abundant elements on the basis of the Sabatier principle is by mixing elements with lower and higher intermediate binding energies. A consistent example is Ni−Cu, which shows a greater HER performance than Ni and Cu in alkaline conditions 93, 94, 95, 96, 97. Another promising material is Ni−Mo;98, 99, 100, 101 however, there have been issues associated with its low dispersion of the active surface.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 95%
“…In this case, the ZnO shell is less uniform than for ZnO@Cu 80 Ni 20 , which is in part due to the less regular morphology of the CuNi foams featuring larger Ni contents. [35] This is because there is strong dependence of the Ni content on the CuNi morphology. Cu deposition typically promotes the formation of a uniform foam-like architecture.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the incorporation of other metals to Ni (smaller values of ∆G H as compared with other earth abundant metals) to form alloys such as NiCo, NiMo, NiCu and ternary metal alloys such as NiMoZn is a promising method to produce electrocatalysts with enhanced HER performances. In addition, synergetic effects can be observed if two transition metals are combined, increasing conductivity [242][243][244][245][246][247][248][249][250][251][252][253][254], making Ni-Co alloys efficient electrocatalysts due to improved intrinsic catalytic activities and corrosion resistance behaviours in alkaline media. For example, Sun et al [243] reported the synthesis of mesoporous NiCo alloys through the electroless deposition method by using different compositions of lyotropic liquid crystals (LLC) as the mesoporous template.…”
Section: Ni-based Alloysmentioning
confidence: 99%